Estimasi Cadangan Klaim Individu untuk Klaim Short-Tailed dan Long-Tailed Menggunakan Algoritma Backpropagation - Rabdika, Anas Satriya; Azizah, Azizah (Department of Mathematics, Universitas Negeri Gorontalo, 2026)
In insurance, risk can occur at any time, causing claims to sometimes have a large amount of value, so that insurance companies may not be able to satisfy claim payments. If these situations occur, insurance companies need claim reserves to prepare for such events. There are several methods to calculate claim reserves, such as aggregate claim reserving. However, certain claim characteristics involve dependencies among claims, which result in a lack of detailed information for individual claims. In addition, an increasing number of claims becomes more difficult to compute using traditional methods. Therefore, this research aims to calculate individual claim reserves using one branch of machine learning, namely the Backpropagation Algorithm. The Backpropagation Algorithm is believed to remain relevant compared to other algorithmic models because, in several studies, it produces relatively low values of Mean Absolute Percentage Error (MAPE), at approximately 2.70%. The data used in this research are simulated using R software, generating 10,000 claims over 20 years, consisting of 6,000 short-tailed claims and 4,000 long-tailed claims. The data model is evaluated using MAPE. The resulting MAPE value is 0.55%, indicating that the data are highly suitable for predictive modeling. The prediction results show that the total claims to be paid in the 21st development year reach Rp22,945,450,000,000, with an average claim amount of approximately Rp2,294,545,152. This research contributes to both informatics and actuarial science by developing an individual claim reserving approach to predict claim payments more efficiently.